ASSESSING THE FINANCIAL SUSTAINABILITY OF THE PENSION SYSTEM OF GEORGIA AND EU27 COUNTRIES AND DEVELOPMENT PROSPECTS IN THE CONDITIONS OF ECONOMIC SHOCKS CAUSED BY COVID-19 (International Journal of Innovative Technologies in Economy, 2020)
Against the background of ongoing demographic change around the world, pension policies have acquired special significance in recent decades. Along with prolonging the population life and reducing the birth rate, the need to reform pension systems has become on the agenda, its main goal is to reduce fiscal pressure in macroeconomic terms, and on a micro scale, ensuring a decent old age with adequate income for retirees. According to the International Monetary Fund the share of state pensions in the GDP of developed and emerging economies will increase by 1-2.5% by 2050. Which calls into question the financial sustainability of many countries' pension systems. In the following study, in parallel with the current events in the world (which implies the economic crisis caused by Covid-19), we will assess the financial sustainability of the Georgian pension system together with the pension systems of E27 countries and determine possible directions for the development of pension systems in the face of economic shock.